The Scientific Image in Behavior Analysis - Keenan, Mickey (Behav Anal, 2016)
Throughout the history of science, the scientific image has played a significant role in communication. With recent developments in computing technology, there has been an increase in the kinds of opportunities now available for scientists to communicate in more sophisticated ways. Within behavior analysis, though, we are only just beginning to appreciate the importance of going beyond the printing press to elucidate basic principles of behavior. The aim of this manuscript is to stimulate appreciation of both the role of the scientific image and the opportunities provided by a quick response code (QR code) for enhancing the functionality of the printed page. I discuss the limitations of imagery in behavior analysis (“Introduction”), and I show examples of what can be done with animations and multimedia for teaching philosophical issues that arise when teaching about private events (“Private Events 1 and 2”). Animations are also useful for bypassing ethical issues when showing examples of challenging behavior (“Challenging Behavior”). Each of these topics can be accessed only by scanning the QR code provided. This contingency has been arranged to help the reader embrace this new technology. In so doing, I hope to show its potential for going beyond the limitations of the printing press.